2017
DOI: 10.1016/j.drugalcdep.2017.01.047
|View full text |Cite
|
Sign up to set email alerts
|

Development and initial validation of a cessation fatigue scale

Abstract: Background Smoking cessation fatigue, or tiredness of attempting to quit smoking, has been posited as a latent construct encompassing loss of motivation, loss of hope in cessation success, decreased self-efficacy, and exhaustion of self-control resources. Despite the potential clinical impact of characterizing cessation fatigue, there is currently no validated measure to assess it. Using a rational scale development approach, we developed a cessation fatigue measure and examined its reliability and construct v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 34 publications
6
16
0
Order By: Relevance
“…In this study, we found several sociodemographic variables that predicted cessation fatigue. Younger quitters reported higher cessation fatigue, consistent with findings from two prior studies (Heckman et al, 2018;Mathew et al, 2017). Higher education was associated with higher fatigue.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…In this study, we found several sociodemographic variables that predicted cessation fatigue. Younger quitters reported higher cessation fatigue, consistent with findings from two prior studies (Heckman et al, 2018;Mathew et al, 2017). Higher education was associated with higher fatigue.…”
Section: Discussionsupporting
confidence: 88%
“…This study also provides insights about factors associated with cessation fatigue which may provide clues about how cessation fatigue influences risk of relapse. In general, the findings from this population-based study on correlates of cessation fatigue correspond to those from studies based on convenience samples of smokers and those recruited for treatment studies (Bekiroglu et al, 2017;Heckman et al, 2018;Liu et al, 2013;Mathew et al, 2017;Piper et al, 2011). In this study, we found several sociodemographic variables that predicted cessation fatigue.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations